2018
DOI: 10.1177/0033688218765306
|View full text |Cite
|
Sign up to set email alerts
|

Exploring EFL Learners’ Accent Preferences for Effective ELF Communication

Abstract: This study explores Chinese English as a foreign language (EFL) learners’ attitudes towards accent for effective English as a lingua franca (ELF) communication. Notwithstanding the research conducted on EFL learners’ perceptions of different variations of the English language for their language learning, little attempts have been made to investigate their perspectives in detail within the context of China. This inquiry thus intends to bridge this gap by exploring EFL learners’ accent preferences for ELF commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
4
11
0
Order By: Relevance
“…The first factor, American English exposure, expressed the greater use of the facilities associated with American English accent and revealed that those who prefer the American English accent over British are exposed more to the American facilities. This confirms both Kung and Wang (2018) and Ahn's (2011) study considering the fact that the proponents of this accent have been exposed to American English accents more than the other varieties and that they rarely experience listening to other varieties. Students` lack of exposure toward other varieties of English is also confirmed by Billiris (2011).…”
Section: Discussionsupporting
confidence: 85%
“…The first factor, American English exposure, expressed the greater use of the facilities associated with American English accent and revealed that those who prefer the American English accent over British are exposed more to the American facilities. This confirms both Kung and Wang (2018) and Ahn's (2011) study considering the fact that the proponents of this accent have been exposed to American English accents more than the other varieties and that they rarely experience listening to other varieties. Students` lack of exposure toward other varieties of English is also confirmed by Billiris (2011).…”
Section: Discussionsupporting
confidence: 85%
“…Regarding language attitudes, Chinese EFL learners generally still prefer the exonormative NS model (e.g. Fang and Ren, 2018; Kung and Wang, 2019). While it is important for English language teaching (ELT) practitioners to inform students of the growing trend of ELF, teachers should support those who aspire to follow the exonormative NS model and inhibit non-target-like pronunciation features.…”
Section: Discussionmentioning
confidence: 99%
“…If such ideologies are allowed to persist, the newly introduced WE and ELF pedagogies, which aim to address realistic communication, would most likely be too far-flung to produce any proactive results (Buripakdi, 2012; Fang and Widodo, 2019; Jenkins, 2007; Jindapitak, 2019). We realize that previous literature on this topic examined the attitudes of particular cultural groups (Jindapitak, 2019; Kung and Wang, 2019; Lim, 2016), including some studies conducted by this article’s researchers (Boonsuk and Ambele, 2019; Fang, 2020). Furthermore, previous studies on accent attitudes towards international students’ own English accents and those of others in the Thai context are limited.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Based on previous studies, it can be concluded that English learners have entrenched attitudes towards English accents, as most of them prefer native Englishes in which the Anglophone varieties of English are viewed as the more authentic models of ELT (Fang, 2020; Jenkins, 2007; Kung and Wang, 2019; Tokumoto and Shibata, 2011). These biases are placed upon NNSE with severe pragmatic negligence on the communicative advantages of accents.…”
Section: Literature Reviewmentioning
confidence: 99%